Transfer pricing in corporate economics perspective: Empirical evidence on the role of interest expenses, R&D investment, total assets, and intangible assets - Prabowo, Sakti; Marfiana, Andri; Wijaya, Suparna; Irawan, Ferry (WIM Solusi Prima, 2025)
This research examines the influence of interest expenses, research and development (R&D) investment, total assets, and intangible assets on transfer pricing aggressiveness in the electronics industry sector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. Within the framework of corporate economics, transfer pricing is not merely a tax compliance instrument but an integral part of corporate strategy in managing cost structure and group-level profitability. This study employs a quantitative approach with panel data regression analysis on a sample of 29 electronics companies, resulting in 116 firm-year observations. The findings indicate that interest expenses and R&D investment have a significant positive effect on transfer pricing aggressiveness, while total assets show a significant negative effect. Conversely, intangible assets do not demonstrate a significant effect on transfer pricing aggressiveness. These results confirm that companies with high leverage and intensive innovation tend to use transfer pricing more aggressively to optimize their global tax position. However, larger companies with substantial total assets appear to adopt more conservative strategies, likely due to concerns about reputation risk and regulatory scrutiny. The absence of a significant effect from intangible assets may reflect effective regulatory enforcement in Indonesia, particularly with the issuance of Minister of Finance Regulation (PMK) No. 172 of 2023, which strengthens the implementation of the Arm's Length Principle and documentation requirements for related party transactions. The implications of these findings provide important insights for tax authorities regarding priority areas of supervision and enforcement, particularly for companies with complex financial structures and intensive innovation. For companies, these findings emphasize the importance of balancing tax efficiency with legal compliance and long-term reputation preservation. Further research is recommended to explore the moderating effect of tax rates, corporate governance, and ownership structure on the relationship between these variables and transfer pricing aggressiveness.